Akhlakul Karimah Sebagai Pondasi Utama: Urgensi Strategi Guru PAI dalam Menanamkan Akhlakul Karimah Siswa - Ulfi Annisa Putri; Fathul Jannah; Agus Setiawan (Badan Penerbit STIEPARI Press, 2025)
This study examines the strategies of Islamic Religious Education (PAI) teachers in instilling akhlakul karimah values as the main foundation for student character development. The findings show that teacher role modeling and habituation are key strategies in the internalization of moral values. Moreover, the application of varied and interactive teaching methods and media significantly enhances students’ interest and understanding. Success measurement is conducted through holistic observation of changes in students’ attitudes and habits. The study also identifies challenges such as limited time and environmental influences, which can be addressed through synergy among schools, parents, and the community.